Comparative analysis of husk microstructure, fruit quality and concentrations of bioactive compounds of different pomegranate cultivars during low temperature storage. (April 2023) - Liu, Qianting; Guo, Xiaohong; Du, Jiaming; Guo, Yidan; Guo, Xiaocheng; Kou, Liping
Abstract: The deterioration degree of pomegranate husk, aroma components and antioxidant contents of pomegranate juice have important effects on postharvest storage quality and vary among cultivars. At the present study, 'Tunisia soft seed', 'Jingpitian' and 'Lishanhong' cultivars from Shaanxi, China was used as raw materials. They were stored at 4 ± 0.5 °C and 85–90% relative humidity for 90 d which aimed to elucidate storability differences. Both husk changes and storage quality were monitored. Our results showed that 'Tunisia soft seed' maintained a good microstructure in husk and possessed a high value of soluble solids/titratable acid ratio and high contents of antioxidants (total phenols, total flavonoids, total anthocyanins, vitamin C) but suffered from high moisture and volatile aroma compounds losses. 'Jingpitian' exhibited lower moisture and aroma compounds losses, but showed significant husk browning, micro-cracks widening, lenticels blocking and wax layer disintegrating. 'Lishanhong' showed similar fruit quality characteristics to 'jingpitian'. These findings will contribute to elucidating the appearance change, microstructure and fruit quality differences among cultivars in postharvest pomegranates during cold storage and providing help for enterprises to discriminate and select varieties suitable for fresh sales or storage. Graphical abstract: Image 1 Highlights: Fruit quality of three pomegranate cultivars was compared during cold storage. 'Tunisia soft seed' had higher contents of the soluble solids and antioxidants. 'Jingpitian' was easier to have cracks widening, lenticel blocking and wax layer disintegrating under SEM. Aroma compounds suffered different degrees of loss. The quality of pomegranate was related to changes of pomegranate husk.